Mitigating money laundering through crypto asset classification in South Africa - Moleko, Mosele Emely (Rhodes University, 2026)
Despite ongoing efforts by academics and international organisations, the classification of crypto assets remains controversial, and their legal status is uncertain in jurisdictions such as South Africa. It can be argued that crypto assets do not fit neatly into existing legal frameworks, but there is a need to develop a global legal benchmark that ensures that crypto assets are subject to the same standards as traditional financial instruments. Global prudential standards should be a yardstick for the development of uniform regulatory frameworks. The pace at which blockchain and crypto asset technologies evolve can render regulations quickly outdated. Rigid regulatory frameworks may fail to adapt to new developments, leading to a misalignment between policy and practice. A flexible regulatory approach that can evolve alongside technology is essential for fostering a healthy ecosystem. On one side, there is a pressing need to protect consumers and the financial system from potential risks, while on the other, overly stringent regulations could stifle innovation and hinder the growth of a transformative sector. Policymakers, academics, and industry leaders are increasingly advocating for a balanced approach that fosters technological advancement while managing associated risks effectively. The overarching goal for global jurisdictions should be the promotion of greater consistency in the classification, regulation and oversight of crypto asset activities. Crypto classification is crucial as different asset types give rise to various legal consequences. This study aims to investigate the implications of regulatory deficiencies stemming from inadequate classification of crypto assets, particularly in relation to crypto asset money laundering. As the use of crypto assets and other digital assets continues to increase, regulatory frameworks in various jurisdictions have struggled to keep pace with the evolving landscape, leading to significant gaps in oversight. These deficiencies often create opportunities for illicit activities, such as money laundering and market manipulation, which can undermine the integrity of financial systems and harm investors. The study highlights the importance of consistent and robust classification schemes that accurately reflect the nature and risk profile of different crypto- assets. Ultimately, the study advocates for the establishment of standardised regulatory frameworks and cross-border cooperation to ensure the effective governance of crypto asset activities, fostering a safer and more transparent digital socio-economy.
Keywords: Uncatalogued